Oxidative stress‐mediated autophagic cell death participates in the neurotoxic effect on SH‐SY5Y cells induced by excessive iodide. Issue 8 (19th June 2018) - Liu, Hongliang; Wang, Lingzhi; Zeng, Qiang; Zhao, Liang; Cui, Yushan; Hou, Changchun; Zhang, Bin; Zhang, Zushan; Zhang, Shun; Chen, Xuemin; Wang, Aiguo
Abstract: Excessive iodide could induce intellectual damage in children, which has attracted broad attention. To investigate the neurotoxic effect of iodide and its mechanism, a human dopaminergic neuroblastoma cell line (SH‐SY5Y) was treated with different concentrations of potassium iodide (KI). The results showed that excessive iodide could decrease cell viability, reduce glutathione (GSH) and superoxide dismutase (SOD), and increase the degree of autophagy (by changing the cellular ultrastructure and raising the autophagy‐related mRNA and protein expression of LC3, Beclin1, and p62), which were correlated with the immunofluorescence labeling. Furthermore, treatment with the autophagy inhibitor 3‐methyladenine (3MA), antioxidant N ‐acetylcysteine (NAC) and 30 mM KI for 24 h was conducted in the following research. 3MA significantly decreased autophagy‐related mRNA and protein expression and improved cell viability, indicating that excess iodide induced autophagic cell death. In addition, oxidative stress regulated autophagy, reflected by the results that NAC decreased the mRNA and protein expression of LC3, Beclin1, and p62. In summary, autophagic cell death mediated by oxidative stress may participate in excessive iodide‐induced SH‐SY5Y cell death.